Assessing the role of network topology, demand variations and recovery strategies in road network resilience - Sohouenou, Philippe (2022)
Road networks are critical to society as they support people's daily mobility, the freight industry, and emergency services. However, a range of predictable and unpredictable events can affect road networks, disrupting traffic flows, connectivity, and, more generally, the functioning of society. With the increased interconnectivity and interdependency of the economic sectors, the need to manage this threat is more critical than ever. To this end, stakeholders need to understand the potential impacts of a multitude of predictable and unpredictable events. The present thesis aims at developing a framework to evaluate and understand the resilience (ability to sustain, resist and recover from perturbations) of road networks under a multitude of potentially unpredictable disruptions, and at assessing the role of different network design (e.g. network topology) and operation (e.g. travel-demand distribution) characteristics in road network resilience.